Flexural Performance Numerical Model Analysis of Transverse Welded Joints in Prefabricated Diaphragm Walls - CUI Tao (Chengshi guidao jiaotong yanjiu)
［Objective］The transverse joints within the panels of prefabricated diaphragm walls are the weak points in the entire wall structure. Therefore, it is necessary to study the stiffness and strength characteristics of these joints. ［Method］In conjunction with prefabricated diaphragm walls commonly used in foundation pit engineering, a new type of transverse welded joints for prefabricated diaphragm walls is introduced. The force and deformation behavior of this new joint under bending moment actions are studied using numerical simulation methods. ［Result & Conclusion］Under bending moment actions, the tensile stress in the concrete at the end of the angle steel on joint tensile side is the highest, while the compressive stress in the concrete at this position on joint compressive side is the highest. The failure of the joint begins with cracks of the concrete on tensile side. The deflection curve of the component shows no significant mutation at the joint, indicating good deformation performance of the joint, which effectively prevents water leakage. The stress in the angle steel, weld, and rebar on joint tensile side is greater than that on the compressive side. After cracks appear in the concrete on the tensile side, the stress in the angle steel, weld, and rebar of the prefabricated component remains at a low level.